Innovation in Islamic finance: The way forward - Hasan, Aznan; Darwar Khan, Sarfaraz; Noordin, Nazrul Hazizi (International Islamic University Malaysia, 2016)
Developing modern Islamic financial products can be very challenging due to a number of constraints from different aspects, including the formation of regulatory, taxation and economic frameworks that are based on conventional principles. Much emphasis was given to replication of conventional instruments by restructuring conventional financial products according to the Islamic law of commercial contracts and eliminating prohibitory elements from these products. This paper aims to discuss the role of innovation in structuring contemporary Islamic financial products. A series of library research is conducted by reviewing both classical and contemporary texts in areas relevant to the present study. In addition, we conducted a field study of the practice of financial innovation made by the stakeholders of the Islamic finance industry. It was found that though replication is acceptable, its continuous application may not be suitable. Hence, it is important for shari’ah scholars and industry experts to think beyond replication. The novelty of this paper lies in the proposed guidelines for innovating Islamic financial instruments.